ANALISIS PENGARUH ATRIBUT PRODUK ISLAMI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH DAN LOYALITAS NASABAH PADA PT BANK NEGARA INDONESIA SYARIAH (BNI SYARIAH) PEKANBARU - Rutmaira Sitinjak; Jushermi '; Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The main purpose of this research to analysis the influence of islamic attribute product and service quality to customer satisfaction and customer loyalty on PT. Bank Negara Indonesia Syariah (BNI Syariah) Pekanbaru. The population of this study are customer of Bank Negara Indonesia Syariah(BNI Syariah) Pekanbaru, with 100 respondents as the sample selected using purpossive sampling method. Meanwhile, quantitative and qualitative methods using path analysis by SPSS versi 21.0. The result of this research show that, Islamic attribute product and Service quality have positive and significant influence on Customer Satisfaction. Islamic attribute product and Service quality have positive and unsignificant influence on Customer Loyalty. Customer Satisfaction has positive and significant influence on Customer Loyalty. Meanwhile, Islamic attribute product and Service Quality have medium influence on Customer Loyalty with Customer Satisfaction as moderating variable. Researcher suggest the company to take notice of Islamic attribute product and maintain service quality received by Customer to increase Customer Satisfaction and Customer LoyaltyKeywords: Islamic Attribute Product, Service Quality, Customer Satisfaction, and Customer Loyalty